2016
DOI: 10.1177/1403494816683454
|View full text |Cite
|
Sign up to set email alerts
|

Drawing on healthcare professionals’ ethnicity: lessons learned from a Danish community pharmacy intervention for ethnic minorities

Abstract: Involving healthcare professionals with ethnic minority backgrounds in encounters with ethnic minorities holds potential for the adaptation of services to ethnically diverse populations, thus improving access to and quality of care. However, it is important to ensure sufficient personal and organisational support and to acknowledge the delicate balance between simultaneously serving as a peer and as a professional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…A qualitative study on the involvement of HCPs with ethnic minority backgrounds in consultation with migrant patients showed that use of bilingual HCPs has the potential to improve quality of health for migrant patients but also has downsides to take into consideration. 38 Another way to address cultural gaps between HCPs and patients is through education in cultural competences 39 and raising cultural awareness among HCPs. 36 This can enable HCPs to address and handle problems related to cultural differences 40 instead of pushing a problem forward to the next HCP who meets the patient, thus creating a snowball effect.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study on the involvement of HCPs with ethnic minority backgrounds in consultation with migrant patients showed that use of bilingual HCPs has the potential to improve quality of health for migrant patients but also has downsides to take into consideration. 38 Another way to address cultural gaps between HCPs and patients is through education in cultural competences 39 and raising cultural awareness among HCPs. 36 This can enable HCPs to address and handle problems related to cultural differences 40 instead of pushing a problem forward to the next HCP who meets the patient, thus creating a snowball effect.…”
Section: Discussionmentioning
confidence: 99%
“…[55]. A Danish study highlighted that involving pharmacists with ethnic minority backgrounds in encounters with ethnic minorities improves access and quality of care [56]. Alternatively, implementing online translation tools, e.g., Google Translate and MediBabble may also enhance the quality of care and satisfaction among patients as well as among healthcare providers [52].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the examined studies were collected in a manner analogous to purposeful sampling. 46 The inclusion criteria resulted in a sample of 40 studies to analyze for this project: two in dentistry/dental hygiene, 47,48 10 in medicine, [49][50][51][52][53][54][55][56][57][58] 10 in nursing, [59][60][61][62][63][64][65][66][67][68] four in occupational therapy, [69][70][71][72] eight in pharmacy, [73][74][75][76][77][78][79][80] two in physical therapy, 81,82 and four in social work. [83][84][85][86] The authors were typically a mix of clinicians (eg, MD), clinician-scientists (eg, RN-PhD), and/or social scientists (eg, PhD in education).…”
Section: Methodsmentioning
confidence: 99%